Peningkatan Dana Anggaran Pendidikan Terhadap Ketimpangan Pendidikan (Studi Kasus: Provinsi Papua) - Putri, Rayinda Sephira; Subroto, Athor (Jurnal Kajian Stratejik Ketahanan Nasional, 2020)
Education is one of the most important factors in the development of a country's progress. Currently, apart from economics and health, education is also an investment and achievement on sustainable development. However, until now education in Indonesia is still not evenly distributed in various regions. There are several areas where education is still not feasible of good quality even though the budget allocation in Indonesia are increasing almost every year, no exception in the Province of Papua. The budget allocation for special autonomy funds in Papua Province is fairly large compared to other parts of Indonesia, what the government is trying to do to improve is to distribute the education sector in Papua Province. The purpose of this study is to explore educational disparities between regions in Papua Province and its relation to the increase in the special autonomy funding budget which is estimated from 2012 to 2018. In this study the researcher uses a quantitative methodology by data panel, namely data time series 2010 to 2018. Combining it with cross section data per city/district in Papua Province, the data is used as a reference in calculating educational inequality in Papua Province using the Gini Index Education where the average length of schooling is the reference. Based on the results of the calculation of educational inequality between regions in Papua Province from 2011 to 2018 it is known that the value of the Gini index calculation of education in Papua Province is included in the category of low or evenly distributed education inequality, this is in line with the results seen by using the Lorenz curve which shows the line 33-35from this calculation, it is found that with the increase in the budget for special autonomy funds every year in Papua Province, the inequality of education in Papua is furthermore getting lower or even. Keywords : Education Inequality, Sustainable development, Lorenz curve, Papua